The role of the insula in the generation of motor tics and the experience of the premonitory urge-to-tic in Tourette syndrome. (May 2020) - Jackson, Stephen R.; Loayza, Joanna; Crighton, Mira; Sigurdsson, Hilmar P.; Dyke, Katherine; Jackson, Georgina M.
Abstract: Tourette syndrome (TS) is a neurological disorder of childhood onset that is characterised by the occurrence of motor and vocal tics. TS is associated with cortical-striatal-thalamic-cortical circuit [CSTC] dysfunction and hyper-excitability of cortical limbic and motor regions that are thought to lead to the occurrence of tics. Importantly, individuals with TS often report that their tics are preceded by 'premonitory sensory/urge phenomena' (PU) that are described as uncomfortable bodily sensations that precede the execution of a tic and are experienced as a strong urge for motor discharge. While the precise role played by PU in the occurrence of tics is largely unknown, they are nonetheless of considerable theoretical and clinical importance, not least because they form the core component in many behavioural therapies used in the treatment of tic disorders. Several lines of evidence indicate that the insular cortex may play a particularly important role in the generation of PU in TS and 'urges-for-action' more generally. In the current study we utilised voxel-based morphometry techniques together with 'seed-to-voxel' structural covariance network (SCN) mapping to investigate the putative role played by the right insular cortex in the generation of motor tics and the experience of PU in a relatively large group of young people TS. We demonstrate that clinical measures of motor tic severity and PU are uncorrelated with one another, that motor tic severity and PU scores are associated with separate regions of the insular cortex, and that the insula is associated with different structural covariance networks in individuals with TS compared to a matched group of typically developing individuals.